2021
DOI: 10.1101/2021.03.30.21254632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coping with COVID-19 Pandemic: A Population-Based Study in Bangladesh

Abstract: This study aims to investigate coping strategies used by Bangladeshi citizens during the COVID-19 pandemic. Design: Prospective, cross-sectional survey of adults (N=2001) living in Bangladesh. Methods: Participants were interviewed for socio-demographic data and completed the Bengali translated Brief-COPE Inventory. Statistical data analysis was conducted using SPSS (Version 20). Results: Participants (N=2001), aged 18 to 86 years, were recruited from eight administrative divisions within Bangladesh (mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The fourth part of the questionnaire contained the validated Bangla version of the 'Brief COPE inventory' which was used to assess the coping strategies of the study subjects [16]. It is a multidimensional measure and presents fourteen scales all assessing different coping dimensions.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…The fourth part of the questionnaire contained the validated Bangla version of the 'Brief COPE inventory' which was used to assess the coping strategies of the study subjects [16]. It is a multidimensional measure and presents fourteen scales all assessing different coping dimensions.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…The COVID-19 pandemic is a stressful circumstance that affects people’s lives and how people cope with the situation needs to be investigated. A study suggested that positive coping, e.g., maintaining emotion and avoiding stress, indicates positive health status but negative coping indicates negative attitudes towards health problems such as poor physical and psychological conditions [ 18 ]. Moreover, the WHO emphasized positive coping mechanisms as an effective approach to dealing with mental health problems under stressful events [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the definition COPING is "Efforts to prevent or diminish threat, harm, and loss, or to reduce the distress that is often associated with those experiences" [17] which can be described as the broad terms "Approach-an issue is solved by controlling stress" and "Avoidant-a problem is solved by avoiding stress by reducing unpleasant emotions". Scholarly evidence shows that Approach Coping Strategy (APC) is more common in the Bangladeshi community than Avoidance Coping Strategy (AVC) [18]. To the best of our knowledge, there is a scarcity of empirical evidence concerning the effects of COVID-19 on coping and QoL among the patients recovering from this infectious disease.…”
Section: Introductionmentioning
confidence: 99%